Complementarity between microarray and immunoblot for the comparative evaluation of IgE repertoire of French and Italian cypress pollen allergic patients - Shahali, Y; Nicaise, P; Brázdová, Andrea; Charpin, D; Scala, E; Mari, A; Sutra, J. P; Chollet-Martin, S; Sénéchal, H; Poncet, P (Folia biologica (Praha), 2014)
Cypress pollen represents the primary cause of respiratory allergies in Mediterranean areas. Patients allergic to Cupressus sempervirens pollen (Cups) (CPA) can be discriminated on the basis of the immunoglobulin E (IgE) binding to a basic 14 kDa protein (BP14) or to high-molecular-weight (HMW) glycoproteins only. Specific IgE repertoires of two differentially exposed CPA cohorts, French and Italian, were investigated using an IgE microarray system (some known major allergens from several allergenic sources) and individual IgE immunoblotting (IB) of whole Cups pollen extract separated by SDS-PAGE (all allergens from one allergenic source: cypress pollen). The prevalence of sensitization to BP14 was higher in French (37 %) than in Italian patients (17 %) and major differences were observed in IgE reactivities to lipid transfer proteins (LTPs). Thirty percent of the Italian CPA (4 % in the French group) had specific IgE against the Parietaria pollen LTP, independently of IB subgroups. Regarding peach LTP sensitization, all Pru p 3+ Italian CPA (10 %) were in the HMW+ subgroup, while Pru p 3+ French CPA (20 %) were all included in the BP14+ subgroup. BP14 sensitization is likely a marker of Cups exposure and is, in French CPA, significantly correlated to Pru p 3 sensitization. The IgE immunoblot and microarray are complementary tools that highlight differences in the subtle sensitization profile between groups of patients in comparative studies.
Keywords: mladiství; Child; Immunoblotting; France; dospělí; imunoglobulin E; transportní proteiny; lidé středního věku; kohortové studie; Humans; Italy; Adolescent; ženské pohlaví; mužské pohlaví; Plant Proteins; cypřiš (rod); Middle Aged; Allergens; imunoblotting; Prevalence; Cupressus; Adult; Immunization; alergie; Francie; Male; pyl; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Pollen; Hypersensitivity; rostlinné proteiny; mladý dospělý; Carrier Proteins; dítě; senioři; lidé; prevalence; Young Adult; alergeny; imunizace; Itálie; Cohort Studies; Immunoglobulin E; Aged; Oligonucleotide Array Sequence Analysis; Female